Late Quaternary evolution of a playa margin at Lake Frome, South Australia. (November 2015) - May, J.-H.; Barrett, A.; Cohen, T.J.; Jones, B.G.; Price, D.; Gliganic, L.A.
Abstract: Playa margins are often characterised by a wide spectrum of landforms, which provide links between major lake stands, as recorded by beach ridges, and the detailed stratigraphic and paleoenvironmental information stored in lacustrine sediments. We mapped playa marginal geomorphology at Lake Frome, South Australia, documented the sedimentary characteristics, and analysed microfossil assemblages in selected sediments. Using a luminescence based approach, the sediments were summarised in four main stratigraphic units. During the later stages of Marine Isotope Stage (MIS)5 fluvio-deltaic sediments were deposited (Unit 1), indicating significant runoff from the adjacent Flinders Ranges into partly freshwater-dominated lakes. No sediments were dated between ∼70 and 25 ka, but renewed sediment delivery from the Flinders Ranges and re-deposition characterised the playa margin LGM and the early Holocene (Unit 2). The most recent phase of depositional activity is reflected by source-bordering dunes and lake marginal spit formation (Unit 3). Short-lived flooding events in the late Holocene are recorded by lake floor sediments and terminal splays (Unit 4). Our findings outline a dynamic late Quaternary playa margin, and highlight the complementary role which playa marginal landforms and sediments may play for the interpretation of runoff, sedimentary dynamics and paleoenvironments related to high regional lake levels. Highlights: Playa margin at Lake Frome links lacustrine and shoreline records. Chronostratigraphy covers >100 ka. Fluvio-deltaic sediments and high local runoff during MIS 5. Lower lake levels during the Holocene. Complex shoreline processes expressed in diverse playa marginal geomorphology.